Bis(phosphinimino)amide Supported Borondihydride and Heteroleptic Dihalo Compounds of Group 131. Issue 15 (27th April 2015) - Jaiswal, Kuldeep; Prashanth, Billa; Bawari, Deependra; Singh, Sanjay
Abstract: The reaction of tetraphenyldiphosphazane (Ph2 P)2 NH with mesityl azide 2, 4, 6‐Me3 C6 H2 ‐N3 affords a new [ N, N′ ] chelating ligand, [HN(Ph2 PN(2, 4, 6‐Me3 C6 H2 ))2 ] (LH ). The ligand can be easily deprotonated by using n BuLi or Li[N(SiMe3 )2 ] in Et2 O to yield [{N(Ph2 PN(2, 4, 6‐Me3 C6 H2 ))2 }Li· OEt2 ] (1 ). The reaction ofLH with AlMe3 and BH3 · SMe2, respectively, gives the corresponding mononuclear complexes [{N(Ph2 PN(2, 4, 6‐Me3 C6 H2 ))2 }AlMe2 ] (2 ) and a rare borondihydride [{N(Ph2 PN(2, 4, 6‐Me3 C6 H2 ))2 }BH2 ] (3 ). Similarly, reaction of1 with the trihalides, MX3, of group 13 elements afford the corresponding dihalo complexes, [{N(Ph2 PN(2, 4, 6‐Me3 C6 H2 ))2 }MX2 ] [M = B, X = F (4 ); M = Al, X = Cl (5 ); M = Ga, X = Cl (6 ); M = In, X = Br (7 )]. All the complexes reported in this work have been isolated in good yields and are expected to serve as useful synthons in a number of reactions. The solid‐state structure ofLH and1 –7 have been investigated by single‐crystal X‐ray structural analysis. Abstract : Synthesis of a rare borondihydride complex has been made possible through the use of a relatively strong donor monoanionic bis(phosphinimino)amide ligand. Crucially, the ligand backbone is void of any reactive acidic hydrogen. The same ligand has also made feasible the synthesis of some heteroleptic dihalo derivatives of group 13 elements.